Sensory and quality evaluation of differently cured snail meat (2013)
Sixty four snails of the Species Archachatina marginata were shelled and the edible part properly washed with clean water. The meat were randomly allotted to four treatments: Wet curing, Dry curing, Wet curing with injection, No curing (control). The meat assigned to the different treatments were cooked with dry heat (grilling) and kept at ambient temperature of2/'C for 14 days. Physical and chemical changes during curing and processing were observed. The pH, processing yield, salt accumulation and sensory evaluation significantly differed (P<0.05) after two weeks of ageing. Snail meats that were wet cured, dry cured and injected with cure (treatments A, B and C) lost much moisture by dripping and evaporation hence, a significant (P<0.05) weight loss was noted in these treatments. Sensory evaluation done showed that the salt content was moderate across treatments. However, wet cured snail meat was ranked best for flavour, tenderness, juiciness and overall acceptability.